Pemikiran Ekonomi Awal: Konsep-Konsep Dasar dan Pengaruhnya Dalam Sejarah Ekonomi - Hasbi, Muhammad; Hidayah, Nurul; Siradjuddin, Siradjuddin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
The history of conventional economic thought starts from the pre-classical era, with Plato as one of the figures who described the ideal economy in the state. The basic concepts of conventional economics include the theory of wants, free markets, social equality, and political discipline to regulate markets. However, the conventional economic paradigm is different from Islamic economics, which is rooted in the teachings of the Koran and hadith. The great contribution of Muslims in the development of economic thought is often overlooked by Western scholars, who tend to skip important periods in history such as the so-called "The Great Gap". In line with Islamic teachings about the use of reason and revelation, Islamic economic thought emerged as a response to economic challenges at certain times. The history of Islamic economic thought can be divided into three phases: the basics phase, the progress phase, and the stagnation phase. The main focus of Islamic economics is on meeting needs, justice, efficiency, growth, and freedom, with the contribution of figures such as Zaid bin Ali, Al-Ghazali, Ibn Taimiyah, and Ibnu Khaldun. Understanding the history of Islamic economic thought has important implications for contemporary economic practice, demanding professionalism, regularity, truth and order in accordance with the principles contained in the Al-Qur'an and the Sunnah of the Prophet.